PENDIDIKAN KARAKTER PADA MADRASAH IBTIDAIYAH DI KOTA SALATIGA - Miftachur Rif’ah Mahmud (Prodi PGMI IAIN Salatiga, 2009)
This qualitative research was conducted to determine the implementation of character education in MIN Gamol, Kecandran, Salatiga. The research problem are how the concept of character education in MI is, how are the methods and strategies of character education, and what are the factors supporting and inhibiting the process of maintaining character education. Research data was collected by interviews which related to the informants, documentation, and field observations. The result shows that the concept of character education in MIN Gamol, Kecandran, Salatiga generally understood as moral education or good moral as a part of character education is less discussed. The emphasized main values are religious, discipline, responsibility, patriotism, nationalism spirit, and achievement appreciation. The method to accustomed character education in MIN Gamol is integrated in all subjects by performing some strategies with habituation, exemplary, discipline, observation and home visit. The educational character is supporting by a young and vibrant teacher, exemplary by school leaders, and students who are ready to respond the tasks from the teacher. The completeness of published documents and the attention of the foundation committee and parents also influence the goals to success. While the inhibiting factors are limited control power of teachers, lack of teachers counseling, inactive parenting club, the condition of school environment and less of parental attention.